MAURICE MERLEAU-PONTY AND THE RESULTS OF HIS THOUGHTS - Ali Mursyid Azisi (IAIN SYEKH NUR JATI, 2020)
Maurice Merleau-Ponty is a philosopher of phenomenology who came from France. From some of his thoughts on several matters, in this case concerning the primacy of perception, the body as a subject, masochism, the unity of taste, and the ambiguity of the experience of taste, it is an interesting discussion to study, especially among academics. Not only that, from the results of his thinking, Merleau-Ponty is also called the